2013
DOI: 10.1093/scan/nst095
|View full text |Cite
|
Sign up to set email alerts
|

Altered emotional and BOLD responses to negative, positive and ambiguous performance feedback in OCD

Abstract: While abnormal processing of performance feedback has been associated with obsessive-compulsive disorder (OCD), neural responses to different kinds of feedback information, especially to ambiguous feedback are widely unknown. Using fMRI and a performance adaptive time-estimation task, we acquired blood oxygenation level-dependant responses and emotional ratings to positive, negative and ambiguous performance feedback in patients and healthy controls. Negative and ambiguous feedback led to increased levels of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…Review articles, in general, ascribe a particular role for the right anterior insula in distress and uncertainty processing (Paulus and Stein, 2006 ; Bach and Dolan, 2012 ; Grupe and Nitschke, 2013 ). But also the right mid anterior insula has been found to be active during conditions of uncertainty (Paulus and Frank, 2006 ; Simmons et al, 2008 ; Sarinopoulos et al, 2010 ; Becker et al, 2014 ) and related to both distress and response inhibition during distress in BPD (Silbersweig et al, 2007 ; Dziobek et al, 2011 ). In comparison to the anterior insula, which provides the highest level of information integration (Craig, 2009 ) and is primarily connected to prefrontal brain regions, the mid insula connects both with prefrontal cognitive-emotional and higher-order sensory regions (Wiech et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Review articles, in general, ascribe a particular role for the right anterior insula in distress and uncertainty processing (Paulus and Stein, 2006 ; Bach and Dolan, 2012 ; Grupe and Nitschke, 2013 ). But also the right mid anterior insula has been found to be active during conditions of uncertainty (Paulus and Frank, 2006 ; Simmons et al, 2008 ; Sarinopoulos et al, 2010 ; Becker et al, 2014 ) and related to both distress and response inhibition during distress in BPD (Silbersweig et al, 2007 ; Dziobek et al, 2011 ). In comparison to the anterior insula, which provides the highest level of information integration (Craig, 2009 ) and is primarily connected to prefrontal brain regions, the mid insula connects both with prefrontal cognitive-emotional and higher-order sensory regions (Wiech et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the left insula is associated with parasympathetic activity and positive affect, the right side is associated with sympathetic activity and distress (Craig, 2005 ). In addition, the right mid-anterior side, specifically, is demonstrated to become activated under conditions of uncertainty (Paulus and Frank, 2006 ; Simmons et al, 2008 ; Sarinopoulos et al, 2010 ; Bach and Dolan, 2012 ; Becker et al, 2014 ) and has previously been related to distress in BPD patients (Dziobek et al, 2011 ) as well as in patients with anxiety disorders (Etkin and Wager, 2007 ). Moreover, a right mid-anterior activity increase has been associated with difficulties in response inhibition in both BPD patients (Silbersweig et al, 2007 ) and non-BPD subjects (Dambacher et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Volumes of interest (VOI) were selected based on 1) the statistical parametric maps generated after full factorial secondlevel analysis for both positive and negative feedback (fcontrast, p < 0.05 FWE-corrected) both for the control and patient group, and 2) on networks assumed to be relevant for the pathophysiology of OCD and/or the processing of reward that have been frequently reported in OCD studies. 1,10,28 These regions are the right and left OFC; the right and left insula; the right and left dorsal striatum/putamen; the right and left visual cortex, considered here to be the region of input to the network as feedback was provided visually; and the vmPFC, connecting the subnetworks from the left and right hemispheres ( Fig. 2).…”
Section: Regions Of Interest For the Dcm Analysismentioning
confidence: 99%
“…During symptom provocation, OCD patients show activation of anterior insula [101,102]; similarly, studies focusing on disgust processing have identified hyperactivity in anterior [103,104] and midposterior [104,105] insula when patients view disgusting images. Further, several paradigms exploring brain functioning in OCD when patients perform cognitive tasks not directly related to symptoms have identified hyperactivity in the insula, including tasks of error detection [106], conflict detection [107], decision making [108], planning [109], response inhibition [110] working memory [111], fearful face processing [112], loss anticipation [113,114], reward [114], and negative performance feedback [115]. Although hyperactivations in these studies are more frequently reported in anterior insula [106][107][108][109][112][113][114] than in mid-posterior insula [110,111,114,115], there are no readily apparent psychological or cohort factors that explain the anterior-posterior differences among studies.…”
Section: Insula Functioning In Anxiety and Ocdmentioning
confidence: 99%